2017
DOI: 10.9775/kvfd.2016.16438
|View full text |Cite
|
Sign up to set email alerts
|

Bıldırcın Rasyonuna Biberiye Uçucu Yağ İlavesinin Büyüme Performansı, Et MDA Düzeyi ve Bazı Plazma Antioksidan Parametreleri Üzerine Etkisi

Abstract: Citation of This ArticleCetin I, Yesilbag D, Cengiz SS, Belenli D: Effects of supplementation with rosemary (Rosmarinus officinalis L.) volatile oil on growth performance, meat MDA level and selected plasma antioxidant parameters in quail diets. Kafkas Univ Vet Fak Derg, 23 (2): 283-288, 2017. DOI: 10.9775/kvfd.2016.16438 AbstractThe current study was conducted to evaluate the effects of dietary supplementation with rosemary volatile oil on performance, meat quality and selected plasma antioxidant parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…These results also agree with Ozarowsk et al, 2013, who found that RO extracts enhanced long-term memory in rats administered scopolamine [13]. This study showed that treatment with RO extract in a rat model of epilepsy led to a decrease in lipid peroxide (MDA) levels, which agrees with the findings of recent studies [38][39][40]. Treatment with RO extract significantly increased antioxidant enzymes, such as SOD, GSH, and GPX; the results of this study agreed with prior studies [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…These results also agree with Ozarowsk et al, 2013, who found that RO extracts enhanced long-term memory in rats administered scopolamine [13]. This study showed that treatment with RO extract in a rat model of epilepsy led to a decrease in lipid peroxide (MDA) levels, which agrees with the findings of recent studies [38][39][40]. Treatment with RO extract significantly increased antioxidant enzymes, such as SOD, GSH, and GPX; the results of this study agreed with prior studies [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…In the view of growth promotion, encapsulated EO supplementation into the diet during the current study did not alter the final body weight, FI and FCR, which is consistent with our earlier report (Kurekci et al, 2014) that showed no apparent efficacy of LMO and α-tops (100 mg/kg) in growth parameters of poultry. In previous experiment (Cetin, Yesilbag, Cengiz, & Belenli, 2017), it was also shown that the supplementation of Rosemary oil at a dose of 250 mg/kg did not change the BW, BWG and FCR in quails. On the other hand, there have been studies showing the beneficial effects of dietary supplementation TA B L E 4 Fatty acid profile (%) and indexes related to human health of breast meat of quails of EO or plant-derived compounds on the growth performance of quails and poultry.…”
Section: Animal Experiments and Growth Performancementioning
confidence: 80%